Draper-mediated and phosphatidylserine-independent phagocytosis of apoptotic cells by Drosophila hemocytes/macrophages. - Manaka, J.; Kuraishi, T.; Shiratsuchi, A.; Nakai, Y.; Higashida, H.; Henson, P.; Nakanishi, Y. (Journal of Biological Chemistry, 2004)
The mechanism of phagocytic elimination of dying cells in Drosophila is poorly understood. This study was undertaken to examine the recognition and engulfment of apoptotic cells by Drosophila hemocytes/macrophages in vitro and in vivo. In the in vitro analysis, l(2)mbn cells (a cell line established from larval hemocytes of a tumorous Drosophila mutant) were used as phagocytes. When l(2)mbn cells were treated with the molting hormone 20-hydroxyecdysone, the cells acquired the ability to phagocytose apoptotic S2 cells, another Drosophila cell line. S2 cells undergoing cycloheximide-induced apoptosis exposed phosphatidylserine on their surface, but their engulfment by l(2)mbn cells did not seem to be mediated by phosphatidylserine. The level of Croquemort, a candidate phagocytosis receptor of Drosophila hemocytes/macrophages, increased in l(2)mbn cells after treatment with 20-hydroxyecdysone, whereas that of Draper, another candidate phagocytosis receptor, remained unchanged. However, apoptotic cell phagocytosis was reduced when the expression of Draper, but not of Croquemort, was inhibited by RNA interference in hormone-treated l(2)mbn cells. We next examined whether Draper is responsible for the phagocytosis of apoptotic cells in vivo using an assay for engulfment based on assessing DNA degradation of apoptotic cells in dICAD mutant embryos (which only occurred after ingestion by the phagocytes). RNA interference-mediated decrease in the level of Draper in embryos of mutant flies was accompanied by a decrease in the number of cells containing fragmented DNA. Furthermore, histochemical analyses of dispersed embryonic cells revealed that the level of phagocytosis of apoptotic cells by hemocytes/macrophages was reduced when Draper expression was inhibited. These results indicate that Drosophila hemocytes/macrophages execute Draper-mediated phagocytosis to eliminate apoptotic cells.